Possibilities of Applying Viscoelastics in Vitreoretinal Surgery - D. V. Petrachkov; A. L. Sidamonidze; K. V. Baryshev; K. N. Shabalina (Oftalʹmologiâ, 2023)
Viscoelastic substances (VS) are an integral part of modern ophthalmic surgery. This review briefly highlights the main characteristics, classification of VS, their areas of application, and their effect on platelet aggregation. In the scientific literature, little attention has been paid to the use of VE in surgery of the posterior segment of the eye; therefore, the main goal of this review was a detailed presentation of the possibilities and prospects for the use of VS in various pathologies of the retina and vitreous body. In vitreoretinal surgery (VRS), cohesive VS are more widely used due to the ease of their removal from the vitreal cavity compared to dispersed VS. The main disadvantage of using VS is their effect on ophthalmotonus, which requires careful monitoring of the completeness of the removal of VEs from the eye at the end of the operation. The review deals with the use of VE in macular pathology for the purpose of mechanical and chemical protection of the retina when working with a luxed lens or introducing dyes that have a toxic effect on the retinal tissue. In macular hole surgery, VS can be used to stabilize the ILM flap, as well as to prevent subretinal migration of retinal dye. The possibilities of using VS in VRS in pediatric practice for the purpose of viscodelamination of retrolental strictures during vitrectomy in eyes with traction vitreoretinopathy and preservation of the native lens are described. Special attention is paid to the use of VS in the most complex surgical pathology requiring VRS — proliferative diabetic retinopathy. Their advantages have been demonstrated in terms of reducing the time of intervention, which, in turn, reduces the risk of intraoperative complications. The use of the viscodissection technique makes it possible to increase the safety of surgery during the most traumatic stages of the operation: separation of the posterior hyaloid membrane and, in particular, when working with proliferative fibrovascular membranes. The advent of the VS staining method opened up new prospects for the use of viscodissection and viscodelamination techniques.